Factors Causing Stress in Health and Community When the Covid-19 Pandemic - Rina Tri Handayani; Saras Kuntari; Aquartuti Tri Darmayanti; Aris Widiyanto; Joko Tri Atmojo (Jurnal Keperawatan Jiwa (JKJ): Persatuan Perawat Nasional Indonesia, 2020)
Various psychological disorders have been reported and published during the Covid-19 outbreak, one of which is stress. Stress is not only felt by the community, even health workers and everyone who works in the medical field. Psychological disorders have a wider and longer-lasting impact compared to physical injuries, while attention to mental health is far less. The purpose of this systematic review is to provide clinical evidence and input for increasing vigilance and self-management to avoid stress during the Covid-19 pandemic. A total of 10 articles from various databases such as PubMed, Google Scholar, NIH, CDC, and Science Direct involving 5925 health workers and 8770 people from various countries have been reported in this systematic review. Factors causing stress on health workers include: workload, fear of being infected with Covid-19, negative stigma of a virus carrier and being away from the family. Factors causing stress to society include: alcohol consumption, workload from home, income, sex, food limitations, and fears of being infected.